Exploring intrinsic motivation and knowledge sharing from the perspective of Islamic teaching - Mansor, Zuraina; Jaharuddin, Nor Siah (Universiti Malaysia Sarawak, 2020)
Every individual has the option whether to share, or not to share their knowledge. Literature suggests that the motivation to share can be influenced by intrinsic or extrinsic factors. Intrinsic factors are normally initiated and are relative to the individual’s interest, or intention. Extrinsic motivation is subject to the work environment, the support system, and the individual’s organisation. Thus, the intention to share can be relative to the environment surrounding the individual. This paper aims to explain the intrinsic motivation factors for Knowledge Sharing (KS)among academics from a public higher education institution in Malaysia. In addition, it was proposed to study intention, and examine whether this was relevant to the concept based on Islamic teaching. Using the explorative study, the paper discussed the results based on a qualitative approach where eighteen academics were interviewed to collect data. Social Determination Theory (SDT) was used and, based on Islamic teaching, the paper study paid particular attention to the concept of brotherhood and ‘ikhlas’ (sincerity).The findings of the study were that academics acting as subject matter experts, understood their role to share knowledge and intrinsic motivation was a significant influence in their willingness to share. Further, based on Islamic teaching, it was found that the concept of ‘ikhlas’,or sincerity, and the concept of ‘happy to help’, or ‘happy to see people happy’, matched and coincided when they shared their knowledge.